2018
DOI: 10.23958/ijirms/vol02-i11/12
|View full text |Cite
|
Sign up to set email alerts
|

The Theory Practices Gap among Nursing and Midwifery Students in Palestine

Abstract: Clinical experience is one of the most significant sources of stress and anxiety producing components of the nursing program. Clinical training, not only gives students the opportunity to transfer what they have learnt during theory into the unfamiliar and complex clinical practice environments. It also helps students learn a variety of skills, such as how to establish communication, make decisions and work as a member of a team. The purpose of this study was to identify nursing and midwifery students’ problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, the study proved that distribution of students’ issues related to some problems with teachers at some point in the clinical practice period. In addition to that, the study found that there was a lack of commitment for the instructors, lack of support, lack of supervision and lack of presence of the instructors with the nursing students during the training period; in addition to that, the clinical instructors are not able to ensure cooperation with ward personnel (Amro et al, 2017).…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study proved that distribution of students’ issues related to some problems with teachers at some point in the clinical practice period. In addition to that, the study found that there was a lack of commitment for the instructors, lack of support, lack of supervision and lack of presence of the instructors with the nursing students during the training period; in addition to that, the clinical instructors are not able to ensure cooperation with ward personnel (Amro et al, 2017).…”
Section: Research Questionmentioning
confidence: 99%
“…All participants completed a self-administered questionnaire in Arabic. The survey instrument consisted of six parts with 42 items to assess the gap adopted from Raso et al (2019), Shahzadi et al (2017), Amro et al (2017), Salah et al (2018) and Mahmoud (2014).…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in some impairment and injury scenarios that occur in schools, the readiness of instructors who have received first aid training to intervene swiftly demonstrates the relevance of this problem (Al-Kubaisy et al, 2019). People who have had this training can act practically and take the necessary life-saving measures before medical assistance arrives, significantly changing the living conditions of those in need (Amro & Qtait, 2017;Das et al, 2020). crisis is what motivates people to begin teaching it to children at a young age and to devote significant resources to furthering education and research in this field (Bakke et al, 2017;Holding et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lecturers, clinical nurses and students are all sceptical about how effective clinical placements are in enhancing skills acquisition among undergraduate students in Ghana. Studies have revealed that there is a gap between what students are taught in class and what they learn during clinical placements ( Adjei et al, 2018;Amro et al, 2017;Jahanpour et al, 2016;Saifan et al, 2015). Registered nurses who act as clinical instructors normally carry out procedures regardless of the standardised way in which students are taught in the class and this confuses students in their clinical learning process (Adjei et al, 2018;Jahanpour et al, 2016)In Ghana, registered nurses generally act as clinical instructors since they are engaged in the clinical teaching of students in the clinical facilities.…”
Section: Introductionmentioning
confidence: 99%